The genome sequence of the Poplar Grey moth, Subacronicta megacephala (Denis & Schiffermüller, 1775) [version 1; peer review: 1 approved, 2 approved with reservations] - Douglas Boyes (Wellcome Open Research)
We present a genome assembly from an individual male Subacronicta megacephala (Poplar Grey moth; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence has a total length of 424.20 megabases. Most of the assembly (99.02%) is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.35 kilobases in length. Gene annotation of this assembly on Ensembl identified 18,189 protein-coding genes.